Heat shock proteins and small nucleolar RNAs are dysregulated in a Drosophila model for feline hypertrophic cardiomyopathy. Issue 1 (27th November 2020) - Tallo, Christian A; Duncan, Laura H; Yamamoto, Akihiko H; Slaydon, Joshua D; Arya, Gunjan H; Turlapati, Lavanya; Mackay, Trudy F C; Carbone, Mary A
Abstract: In cats, mutations in myosin binding protein C (encoded by the MYBPC3 gene) have been associated with hypertrophic cardiomyopathy (HCM). However, the molecular mechanisms linking these mutations to HCM remain unknown. Here, we establish Drosophila melanogaster as a model to understand this connection by generating flies harboring MYBPC3 missense mutations (A31P and R820W) associated with feline HCM. The A31P and R820W flies displayed cardiovascular defects in their heart rates and exercise endurance. We used RNA-seq to determine which processes are misregulated in the presence of mutant MYBPC3 alleles. Transcriptome analysis revealed significant downregulation of genes encoding small nucleolar RNA (snoRNAs) in exercised female flies harboring the mutant alleles compared to flies that harbor the wild-type allele. Other processes that were affected included the unfolded protein response and immune/defense responses. These data show that mutant MYBPC3 proteins have widespread effects on the transcriptome of co-regulated genes. Transcriptionally differentially expressed genes are also candidate genes for future evaluation as genetic modifiers of HCM as well as candidate genes for genotype by exercise environment interaction effects on the manifestation of HCM; in cats as well as humans.